A SUBJECT REVIEW ON THE: ADVANCING ELECTRONIC DEVICES WITH CONDUCTIVE POLYANILINE NANOCOMPOSITE THIN FILMS: CHARACTERISTICS, AND APPLICATIONS - Jarad, Amer N.; Dheyab, Raed A.; Abdulelah, Haider (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to provide a comprehensive review of conductive polyaniline (PANI), emphasizing its synthesis, characterization, nanocomposites, thin films, and diverse applications. The primary goal is to compile the latest findings and advancements, highlighting PANI's potential in materials science and electronics due to its high conductivity and adaptability. Method: The study explores various PANI synthesis methods, including chemical synthesis and electrochemical polymerization. Detailed analyses are conducted on PANI’s properties, such as surface morphology, conductivity mechanisms, doping processes, and structural characteristics. Techniques for manufacturing PANI thin films, including deposition methods and surface modifications, are reviewed alongside characterization approaches used to evaluate their properties. Results: PANI nanocomposites are examined, focusing on their integration into nanomaterials and resulting characteristics. Applications in electronic devices, sensors, biosensors, energy storage, organic electronics, and flexible electronics are discussed extensively. Additionally, methods for enhancing PANI’s performance and characteristics are highlighted, underscoring its practical utility in advanced technologies. Novelty: This review consolidates recent developments in PANI research, offering in-depth insights into its synthesis, structural attributes, and application spectrum. By addressing PANI’s role in emerging technologies such as flexible and wearable electronics, the study underscores its significance and potential for future advancements in materials science and electronic applications.